Uso de recursos tecnológicos en docentes de instituciones educativas periféricas del distrito de Punchana, Loreto 2024 - Navarro Mananita, Ruth del Pilar (2025)
The objective of this study was to determine the level of use of technological resources in teachers of peripheral educational institutions in the district of Punchana, Loreto, during the year 2024. The research was proposed under a quantitative approach, with a simple descriptive design, considering a population of 139 teachers, through stratified probabilistic sampling, a representative sample of 103 teachers was selected, respecting the proportion of each stratum within the population. To collect information, the survey technique and a 50-item Likert-type questionnaire were used. The results showed that 66% of teachers are at a medium level of use of technological resources, which suggests that the majority have basic skills to use digital tools, although they need training for more advanced and efficient use. In technological knowledge, 50.5% also showed a medium level, reflecting functional competencies and a limited understanding of digital resources. Furthermore, 65% present an average use of technological resources, indicating that their integration into pedagogical practice can still improve. Regarding the application of methodological resources, 63.1% of teachers are at a medium level, evidencing intermediate knowledge in the use of technological methodologies. In conclusion, teachers show a regular general level in the management of technological resources, which highlights the importance of strengthening their skills to achieve a more effective and beneficial integration of technology in educational processes.